Pendidikan Kesehatan Tentang Personal Hygiene Dalam Upaya Meningkatkan Derajat Kesehatan Pada Siswa/i di SMA Muhammadiyah Kota Langsa - Ayunin Syahida; Uli Dayanti; Dahlia Linda Vera (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Adolescence is a period of human development where there is a change in both biological, psychological and social. Changes that occur in adolescent girls are characterized by menarche (first menstruation), changes in the chest, growth of pubic hair and also pelvic enlargement. In general, physical health problems in adolescents are often ignored so that it has an impact on physical health in adolescents. Lack of knowledge of personal hygiene can be a factor inhibiting the health of personal hygiene in adolescents. There are several parts of health that need attention by adolescents in the implementation of personal hygiene such as maintaining dental and oral health, skin and facial health, reproductive organ health, daily clothing and care for hair and nails and feet. The purpose of this community service is so that teenagers can know and carry out personal hygiene so that they avoid various health problems. The method used is a lecture by providing counseling about personal hygiene to students to improve their health status and be free from various health problems that often occur in adolescents. The target achieved in the service is to increase students' knowledge about personal hygiene which will later change students' attitudes in performing personal hygiene. Students are expected to take part in counseling activities seriously in order to produce good knowledge and attitudes so that they can change behavior to perform personal hygiene.